After violence : transitional justice, peace and democracy - Skaar, Elin; Gianella Malca, Camila; Trine, Eide (Abingdon, Oxon [England] : Routledge, 2015)
'After Violence: Transitional Justice, Peace, and Democracy examines the effects of transitional justice on the development of peace and democracy. Anticipated contributions of transitional justice mechanisms are commonly stated in universal terms, with little regard for historically specific contexts. Yet a truth commission, for example, will not have the same function in a society torn by long-term civil war or genocide as in a society emerging from authoritarian repression. Addressing trials, reparations, truth commissions, and amnesties, the book systematically addresses the experiences of four very different contemporary transitional justice cases: post authoritarian Uruguay and Peru and post-conflict Rwanda and Angola.'--Page [i].
1. Transitional justice alternatives: claims and counterclaims. -- 2. Towards a framework for impact assessment. -- 3. Uruguay : reconstructing peace and democracy through transitional justice. -- 4. Peru : changing contexts for transitional justice. -- 5. Rwanda : some peace, no democracy, and the complex role of transitional justice. -- 6. Angola : negative peace and autocracy in the shadow of impunity. 7. Conclusions. -- Appendix 1: Truth commissions around the world, 1982-2014. -- Appendix 2 : Statistical measures used in the analysis.
'GlassHouse book.'
Includes bibliographical references and index.
Keywords: Transitional justice -- Case studies; Human rights -- Case studies; Peace-building -- Case studies; Democracy -- Case studies; Truth commissions -- Case studies; Uruguay -- Politics and government -- 20th century; Peru -- Politics and government -- 20th century; Rwanda -- Politics and government -- 20th century; Angola -- Politics and government -- 20th century